Preventing Noise and Vibration During the 60 Years of Activity of the Central Institute for Labour Protection – National Research Institute - ZAWIESKA, Wiktor Marek; PLEBAN, Dariusz (Archives of Acoustics, 2011)
In 2010, the Central Institute for Labour Protection – National ResearchInstitute celebrated the 60th anniversary of its activity. Primary objectives ofthe Institute have been and continue to be the protection of employees againstany hazards at work stations. Among the numerous hazards, vibroacoustic onesare becoming prevailing. Therefore, one can now dare to say that the 60 yearsof activity of the Central Institute for Labour Protection have also meant 60years of preventing noise and vibration in the working environment. For those 60years of activity, Central Institute for Labour Protection has been associated withoutstanding acousticians and vibration specialists. The first chairperson of theScientific Council of the Central Institute for Labour Protection was ProfessorIgnacy Malecki, one of the most outstanding Polish scientists. Chairpersons of theCouncil have also included Professor Adam Lipowczan and Professor ZbigniewEngel and the members of the Council have included Professor Stefan Ziembaand Professor Jerzy Sadowski.In 1956, the Institute established the Department of Vibration Research, furthertransformed into the Department of Technical Acoustics and since 1990 –the Department of Acoustic and Electromagnetic Hazards. The Department wasfounded and for a long time headed by Assistant Professor Czesław Puzyna. FollowingProfessor Puzyna’s retirement, the Department was headed by AssistantProfessor Danuta Augustynska. At present, it is the Department of VibroacousticHazards, since 2007 headed by Dariusz Pleban, Ph.D., Eng.